(untitled) (Research, Society and Development, 2023)
The service offered by the multidisciplinary team, in order to provide comprehensive care to critical patients within their recognized interdependencies, has been increasingly frequent in urgent and emergency settings. In view of the great diversity of professions that can serve and develop a clinical perspective from different professional perspectives. The present study aimed to seek and analyze the evidence that points to the challenges faced by the multidisciplinary health team in the care of urgent and emergency networks, extolling their achievements and importance to teamwork. This is an exploratory research of a qualitative nature, whose reasoning and development were carried out through a bibliographical survey, characterizing itself as an integrative literature review. As a result of the research, a major challenge of multidisciplinary teamwork was the lack of interprofessional communication and sometimes the lack of professional recognition as part of the care team. It can be concluded that there is a lack of studies emphasizing the multidisciplinary team in patient-centered care and the lack of continuing education in urgent and emergency units, emphasizing the need to develop activities that can encourage, stimulate discussions and reflections of a multidisciplinary nature by the teams to so that the teams can develop the decision-making role in the patient’s therapeutic planning in a gradual and interprofessional way.